Analysis of Landslide Vulnerability in Agribusiness Development Efforts Environmental Insight in Ngargoyoso District - Nugraha, Setya; Tjahjono, Gentur Adi (Universitas Sebelas Maret, 2020)
The area of Ngargoyoso Subdistrict, Karanganyar Regency, has geosphere conditions that have the potential to be developed for agribusiness crops, but are prone to landslides. In it’s development, it is necessary to integrate considerations of productivity and land sustainability by considering the carrying capacity of the land through the identification of landslide vulnerabilities. The objectives of this research are: (1) To determine the vulnerability of landslides in the Ngargoyoso District, (2) To determine the direction of land conservation for sustainable agricultural land development in Ngargoyoso District. The unit of analysis is in the form of land unit which is the result of overlapping between rock, soil, slope and land use units. The method of determining landslide vulnerability uses the scoring method of landslide determining parameters. The results of the research were (1) high landslide susceptibility area of 4,797.25 hectares (78.13%), moderate landslide susceptibility area of 1,343.26 hectares (21.87%), and (2) conservation directions in the form of zoning for seasonal agricultural land and manufacturing. terracing by paying attention to the slope and depth of the solum.